2013 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--19548
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Student Comprehension with Video Grading

Abstract: Ph.D. from the University of Toledo. He worked for Ford Motor Company and Visteon as an embedded software engineer for several years prior to returning for doctoral work. He has spent time at NASA Glenn Research Center in Cleveland, Ohio, and consulted for multiple embedded systems companies in the Midwest. In addition to one U.S. Patent, Schilling has numerous publications in refereed international conferences and other journals. He received the Ohio Space Grant Consortium Doctoral Fellowship, and has receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Creation of Video-Based Feedback Mathisen (2012) reported that the process of creating video-based feedback was intuitive for instructors. Many studies reported that providing video-based feedback, required less time than providing written feedback (Denton, 2014;Gonzalez & Moore, 2018;Griffiths & Graham, 2010;Henderson & Phillips, 2015;Lamey, 2015;Mathisen, 2012) or the same amount of time (Crook et al, 2012;Jones et al, 2012;O'Malley, 2011;Schilling & Estell, 2014;Vincelette & Bostic, 2013;West & Turner, 2016). Gonzalez & Moore (2018) found that relying solely on video feedback reduced time spent on each submission compared to written comments.…”
Section: Resultsmentioning
confidence: 99%
“…Creation of Video-Based Feedback Mathisen (2012) reported that the process of creating video-based feedback was intuitive for instructors. Many studies reported that providing video-based feedback, required less time than providing written feedback (Denton, 2014;Gonzalez & Moore, 2018;Griffiths & Graham, 2010;Henderson & Phillips, 2015;Lamey, 2015;Mathisen, 2012) or the same amount of time (Crook et al, 2012;Jones et al, 2012;O'Malley, 2011;Schilling & Estell, 2014;Vincelette & Bostic, 2013;West & Turner, 2016). Gonzalez & Moore (2018) found that relying solely on video feedback reduced time spent on each submission compared to written comments.…”
Section: Resultsmentioning
confidence: 99%
“…Five of the nine students interviewed had watched their feedback at least twice with one watching it six times. Students found written feedback easier to trace, access and review than video feedback because of the 'linearity' of the video format which limits the navigational control that recipients can exert over how they consume the feedback message (Schilling & Estell, 2014). Students must watch the video from beginning to end, whereas with written feedback, students can scan comments in whichever order they wish.…”
Section: Findings Description Of Respondentsmentioning
confidence: 99%
“…Overall, these videos were well received by students. In early studies, students generally preferred video feedback over traditional written feedback [3]. In later work, we were able to demonstrate slight improvements in student achievement on assignments [4] [5] based upon viewing of these feedback videos.…”
Section: Introductionmentioning
confidence: 66%